Factors Affecting Micro Small and Medium Enterprises Taxpayer Compliance at Cilegon Pratama Tax Office - Ainaya Nurulin Nafaril; Yanuar Ramadhan (Borong Newinera Publisher, 2024)
Factors Affecting Micro small and Medium Enterprises Taxpayer Compliance at Cilegon Tax Office. Ainaya Nurulina Nafaril. Master of Accounting Study Programme. The low level of taxpayer compliance in reporting tax obligations greatly affects state revenue. The decreasing level of taxpayer compliance is a bad impact on the state because taxes are an important fund for the state. This study aims to determine the factors that influence Micro small and Medium Enterprises taxpayer compliance at KPP Cilegon. The research method used is the survey method. The results showed that the variables of Taxpayer Understanding, Service Quality and Tax Sanctions had a positive and significant influence on Taxpayer Compliance. While the perceived effectiveness of the tax system variable has a positive and insignificant effect on taxpayer compliance. Therefore, to increase taxpayer compliance, the government needs to make efforts such as the government should increase Micro small and Medium Enterprises taxpayers' understanding of tax regulations through various education and socialisation programs through various media such as seminars, training, and social media. The government needs to improve the quality of services to Micro small and Medium Enterprises taxpayers, both in terms of speed, accuracy and ease of access. The government must be careful in applying tax sanctions so as not to have a negative impact on the economy. The results of this study are expected to provide information to policy makers as a basis for consideration to improve taxpayer compliance.